Predicting population status of freshwater pearl mussel (Margaritifera margaritifera, L.) in central Sweden using instream and riparian zone land‐use data. Issue 2 (10th January 2013) - Degerman, E.; Andersson, K.; Söderberg, H.; Norrgrann, O.; Henrikson, L.; Angelstam, P.; Törnblom, J.
ABSTRACT The freshwater pearl mussel Margaritifera margaritifera (L.) has become scarce and threatened throughout most of its distribution range, and is consequently listed as 'endangered' by the IUCN. It has been suggested and used as an indicator species and even as an umbrella species. Despite this, few studies have examined factors affecting its catchment‐level population status. This work tested the hypothesis that it is possible to predict freshwater pearl mussel population viability (reproducing/not reproducing) and population status in central Sweden from a combination of geospatial data describing riparian land‐cover and use, water chemistry data, and electrofishing data describing the abundance of the host fish species (brown trout, Salmo trutta) in 56 streams. Mussel population viability was best predicted by total phosphorus. Using higher‐resolution data (six classes) on mussel population status, host fish abundance (0+ trout) was the best predictor. At abundances below 5 0+ trout per 100 m2 and above a concentration of 8 µg L–1 total phosphorus, only three viable populations existed. Geospatial data could be used to predict levels of total phosphorus and thereby indirectly to predict mussel viability. Geospatial data could not be used to predict abundance of 0+ trout, which is thought to depend more on instream factors. This study demonstrates that geospatial data on riparian land‐use and cover can be a useful tool for screening waters potentially harbouring non‐reproducing mussel populations. Copyright © 2013 John Wiley & Sons, Ltd.